2017
DOI: 10.4155/fmc-2017-0190
|View full text |Cite
|
Sign up to set email alerts
|

Can Small Molecule Inhibitors of Glutaminyl Cyclase Be Used as a Therapeutic for Alzheimer'S Disease?

Abstract: Alzheimer's disease (AD) is a multifactorial and socioeconomically burdensome disease. In view of the failures of anti-AD candidates, we should try to rethink what we did before and what we should do next, in part at least. Research shows that the more neurotoxic factor, pyroglutamate-Aβs, and the more important inflammatory mediators, pyroglutamate-CCL2, both contribute to the initiation of AD specifically and the generation of N-terminal intramolecular cyclization catalyzed by glutaminyl cyclase quality cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In addition, QC inhibitors are known to effectively reduce the levels of Aβ N3pE and Aβ plaques in the brain, improving memory deficits in AD mice [96–97] . These findings support QC inhibition as a valid therapeutic strategy for AD [98–99] . Manh et al.…”
Section: Benzimidazoles and Benzoxazoles In Alzheimer's Disease Treat...mentioning
confidence: 80%
See 1 more Smart Citation
“…In addition, QC inhibitors are known to effectively reduce the levels of Aβ N3pE and Aβ plaques in the brain, improving memory deficits in AD mice [96–97] . These findings support QC inhibition as a valid therapeutic strategy for AD [98–99] . Manh et al.…”
Section: Benzimidazoles and Benzoxazoles In Alzheimer's Disease Treat...mentioning
confidence: 80%
“…[96][97] These findings support QC inhibition as a valid therapeutic strategy for AD. [98][99] Manh et al investigated new classes of QC inhibitors designed using bioisostere-based, pharmacophore-based and structure-based approaches. Main pharmacophores: it can be classified as zinc-binding groups (pharmacophore A), hydrogen-bonding donors (pharmacophore B), or phenyl groups (pharmacophore C).…”
Section: Benzimidazoles and Benzoxazoles In Alzheimer's Disease Treat...mentioning
confidence: 99%
“…Pyroglutamylated Ab peptides (AbpEs) are found in selfaggregated Ab peptides and act as initiators of Ab accumulation, favoring plaque seeding [115,116]. AbpE is only found in AD brains and constitutes approximately 50% of the total Ab [117], so the level of AbpE has been treated as a potential biomarker of AD [118]. AbpE is upstream of the neurotoxic amyloid cascade, triggering neurodegeneration and enhancing AD pathology [119][120][121].…”
Section: Qc/isoqc In Neuron Diseasesmentioning
confidence: 99%
“…It has also been reported that small-molecule inhibitors of QC efficiently reduced the brain levels of pE-Aβ and Aβ plaques and improved memory deficits in AD mice . These studies suggested that inhibition of brain QC activity may bring about beneficial effects for AD patients. , Several research groups have developed QC inhibitors that are based on imidazole ( 1 ) and benzimidazole core structures ( 2 , 3 ) , (Figure ). The most prominent candidate is PQ912 ( 3 ), developed by Probiodrug, which showed improvement in synaptic and neurological functions in AD patients without significant toxicity in clinical trials. , More recently, Rubinsztein and colleagues introduced an N -methyltriazole-based inhibitor ( 4 , SEN177 ), which was discovered through three-dimensional (3D)-pharmacophore model-based in silico methods .…”
Section: Introductionmentioning
confidence: 98%
“…22 These studies suggested that inhibition of brain QC activity may bring about beneficial effects for AD patients. 25,26 Several research groups have developed QC inhibitors that are based on imidazole (1) 27 and benzimidazole core structures (2, 3) 28,29 (Figure 1). The most prominent candidate is PQ912 (3), developed by Probiodrug, which showed improvement in synaptic and neurological functions in AD patients without significant toxicity in clinical trials.…”
Section: ■ Introductionmentioning
confidence: 99%